Investigating Arabic Vocabulary Writing Errors in Second Language Learning - Lusia Eka Barina Listi; Wulan Indah Fatimatul Djamilah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
This study aims to analyze errors in Arabic vocabulary writing made by students at MTsN 1 Surabaya. The main focus of this study is to identify the types of errors that occur most frequently and to examine the factors behind these errors. This study employs a qualitative descriptive method, utilizing data collection techniques such as documenting students' written work and conducting interviews with Arabic language teachers. The data obtained are analyzed to identify patterns of errors and their underlying causes. The results of the study indicate that the most dominant errors include mistakes in letter writing, spelling errors, and inaccuracies in writing word forms due to a lack of understanding of Arabic morphological structure. Other contributing factors include insufficient regular writing practice, limitations in the learning materials used, and a lack of mastery of the meanings of vocabulary taught in class. These conditions show that students' writing skills still require intensive training, especially in terms of accuracy and consistency in the use of correct vocabulary. This study is expected to serve as evaluation material for teachers in designing more effective, creative, and varied learning strategies, thereby improving writing skills, strengthening vocabulary mastery, and fostering student motivation in learning Arabic continuously, both in school and in everyday life.